2018
DOI: 10.7556/jaoa.2018.006
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ultrasonography on Student Learning of Shoulder Anatomy and Landmarks

Abstract: Ultrasonography in the preclinical curriculum may improve medical students' confidence in and accuracy of palpation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 8 publications
0
14
0
Order By: Relevance
“…Our findings are consistent with those of other recent studies of MSK US in medical education. de Vries et al evaluated first‐year medical students at an osteopathic medical school and found that students with MSK US experience along with traditional anatomic instruction had greater levels of confidence and accuracy in evaluating anatomic landmarks of the shoulder. Woods et al also evaluated the use of US for improving the palpation skills of physicians in training and found that after US instruction on the skill of locating the long‐head biceps tendon, the accuracy of palpating the tendon improved from 20% to 52%.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are consistent with those of other recent studies of MSK US in medical education. de Vries et al evaluated first‐year medical students at an osteopathic medical school and found that students with MSK US experience along with traditional anatomic instruction had greater levels of confidence and accuracy in evaluating anatomic landmarks of the shoulder. Woods et al also evaluated the use of US for improving the palpation skills of physicians in training and found that after US instruction on the skill of locating the long‐head biceps tendon, the accuracy of palpating the tendon improved from 20% to 52%.…”
Section: Discussionmentioning
confidence: 99%
“…Through additional ultrasound sessions, we also hope to not only increase confidence in those who are less confident but also to increase student confidence in physical exam maneuvers [24,25]. Anatomy, physical examination skills, and confidence in sonography can all be addressed through additional didactic and hand-on ultrasound sessions.…”
Section: Total N 18mentioning
confidence: 99%
“…The results of the scoring data analysis showed a signi cant improvement in the accuracy of palpation, rather than speed, leading to an increase in the overall score. By using US images, students can learn the palpation technique by obtaining visual feedback 5,13 . This might be one of the reasons why the students recruited in our study obtained more accurate palpation skills for each landmark.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, systematic learning courses for improving palpation skills using US images have been developed to take advantage of the US images recently 10 . There has also been an increasing number of interventional studies on the usefulness of US imaging as a tool to improve the palpation skills of medical students or residents [11][12][13][14][15] .…”
Section: Introductionmentioning
confidence: 99%